Formulation and evaluation of orally disintegrating clopidogrel tablets - Gamal Mohamed Mahrous; Mohamed Gabr Kassem; Mohamed Abbas Ibrahim; Sayed Hassan Auda
ABSTRACT Recent advances in drug delivery systems have aimed to achieve better patient compliance. One of these advances is the formulation of orally disintegrating tablets (ODTs) that dissolve instantaneously, releasing drugs within a few seconds without the need of water. The main objective of this paper was to prepare and develop ODTs of clopidogrel. The ODTs were prepared by direct compression. The effect of three superdisintegrants, namely crospovidone, croscarmellose sodium, and sodium starch glycolate, using three different disintegration times on the dissolution rate was investigated. The prepared tablets were evaluated for hardness, friability, disintegration time and in vitro drug release. Furthermore, the interaction of clopidogrel with the formulation excipients was studied using differential scanning calorimetry (DSC). DSC studies revealed that there were no interactions between the drug and the excipients used. All tablets had hardness values in the range 4.0-5.2 kp and friability lower than 1%. The weight and drug content uniformity of all formulations was within official limits according to BP. In vitro drug release studies of the ODTs showed that more than 90% of the drug was released within ten minutes. A palatability test in human volunteers showed acceptable taste and mouth feel. Thus, the obtained results conclusively demonstrated successful rapid disintegration of the formulated tablets and acceptable palatability.